(untitled) (مجلة المنصور, 2022)
This research deduced from the subject that national court authority must be viewing in to acts against natural persons or moral’s that they make crimes described in to interfacing authority with some excepting. Otherwise the international courts joining with authority wider more than national authority without missing the national authority unless the circumstances that cannot ability to Judge the persons who their crimes are called internationality. So under all these thinks this research will be divided in to three parts chapter one will be defined all content as competences theory as generally, the second chapter explain the competences of courts national and (International), under all Two criminals acts will be determined and finally chapter three is to explain if there is a conflict between the two courts or more suitable. Under all these in above this research is to investigating and insuring that there is deeply infraction in the basis system of decisions to security council authority Idle, stopping the investigating or juridical for personal not shortly with under as renewing and discussed to a abolish all the paragraph (B) from the article number (13) in the system .